Unilateral pulmonary agenesis in a child with recurrent respiratory tract infections - Das, Rajib; Roy, Priti (International Journal of Research in Medical Sciences, 2022)
Pulmonary agenesis is a rare congenital anomaly defined as complete absence of lung parenchyma with its bronchial tree and vasculature. It usually presents in early childhood and may be associated with other congenital abnormalities. Chest X-ray gives a suspicion of this condition which can be further confirmed by computed tomography scan of thorax. Oher investigations like echocardiography and ultrasonography of whole abdomen must be done to rule out associated congenital anomalies. We describe here a case of one month old male who presented with cough and shortness of breath. Chest X-ray showed right sided homogenous opacity which on contrast enhanced computed tomography revealed right sided pulmonary agenesis. Echocardiography showed situs solitus with dextroposition of heart. The child was treated with intravenous antibiotics, moist oxygen and nebulisation with bronchodilators following which there was clinical resolution of symptoms. In conclusion, congenital pulmonary agenesis should be included in the differential diagnosis in a child presenting with dyspnoea and homogenous opacity of unilateral lung field in Chest X-ray for early diagnosis, management and prevention of recurrent respiratory infections and consequently to reduce childhood mortality.